Developing Spiritual Intelligence Through The Internalization of Sufistic Values: Learning From Pesantren Education - Abidin, Zainal; Sirojuddin, Akhmad (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study aims to analyze and describe the concept and implementation of spiritual intelligence development through the internalization of Sufi values within the Islamic boarding school education system. The method employed in this research is a qualitative approach using a case study method. The case studied in this research is the interconnected system within Islamic boarding schools in developing spiritual intelligence through the internalization of Sufi values. Findings from this research indicate that the development concept. The research utilizes a qualitative approach with a case study method. The case examined in this research is the development of spiritual intelligence through the internalization of Sufi values supported by the sub-system of Islamic boarding schools. The findings of this research are: (1) the transformation of Sufi values is divided into three domains: individual-social, vertical-horizontal, and human-cosmic. This development is carried out with rational values such as social sciences, natural sciences, and humanities, (2) the transaction of Sufi values is supported by the Sufi environment of the Islamic boarding schools such as dhikr (remembrance of God), spiritual struggle (mujahadah), thariqah rituals, and beneficial admonitions (mauidloh hasanah), (3) the transinternalization of Sufi values to develop spiritual intelligence is developed through academic environments such as research, discussion, and interaction.